Religious Transition from Islam to Non-Islam: Legality, Sanctions, and Procedures in Indonesia and Malaysia - SAPUTRA, Deris Arista (PT. Keberlanjutan Strategis Indonesia, 2025)
Purpose:The urgency of this topic lies in the increasing tension between religious norms, individual constitutional rights, and the implementation of positive law, which is often ambiguous or repressive. This study aims to systematically analyze and compare the legal aspects, sanctions, and administrative procedures of conversion from Islam in both countries.Methodology:This study uses a qualitative approach with a normative-comparative method, utilizing secondary data in the form of legal regulations, court decisions, and current academic literature. The analysis is carried out through document studies and content analysis of the national legal framework and religious institutions that play a role.Findings:The results of the study show that Malaysia has a more structured legal system through the Sharia Court in regulating applications to leave Islam, although the procedures tend to be restrictive and accompanied by administrative or criminal sanctions. On the other hand, Indonesia adopts a more flexible administrative approach but is vulnerable to legal uncertainty and social pressure.Implication:The conclusion of this study states that protection of the right to convert requires clear regulations, fair institutions, and inclusive social support. This study suggests the development of future empirical studies to explore the experiences of individual converts and the dynamics of legal implementation at the local level.